2010
DOI: 10.3390/en3121934
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Hydrate Thermal Conductivity

Abstract: Abstract:In this review, the intriguing, anomalous behaviour of hydrate thermal conductivity will be described, and progress in performing experimental measurements will be described briefly. However particular attention shall be devoted to recent advances in the development of detailed theoretical understandings of mechanisms of thermal conduction in clathrate hydrates, and on how information gleaned from molecular simulation has contributed to mechanistic theoretical models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…In addition, it is possible to measure thermal conductivity, thermal diffusivity, and heat capacity per unit volume simultaneously (Gustafsson et al, 1979). It is hard to draw a definite conclusion that which technique is better for pure gas hydrate samples synthesized in laboratory; however, for in-situ determination of the thermal properties of hydrate-containing sediments, the single-sided TPS technique may be more suitable as the needle probe and double-sided TPS techniques need the probe to be surrounded by the hydrates (English and Tse, 2010). There are several factors, such as the porosity of the samples, temperature, pressure, and measurement time, that influence thermal conductivity of gas hydrates.…”
Section: Thermal Conductivity Of Gas Hydratementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is possible to measure thermal conductivity, thermal diffusivity, and heat capacity per unit volume simultaneously (Gustafsson et al, 1979). It is hard to draw a definite conclusion that which technique is better for pure gas hydrate samples synthesized in laboratory; however, for in-situ determination of the thermal properties of hydrate-containing sediments, the single-sided TPS technique may be more suitable as the needle probe and double-sided TPS techniques need the probe to be surrounded by the hydrates (English and Tse, 2010). There are several factors, such as the porosity of the samples, temperature, pressure, and measurement time, that influence thermal conductivity of gas hydrates.…”
Section: Thermal Conductivity Of Gas Hydratementioning
confidence: 99%
“…There are several factors, such as the porosity of the samples, temperature, pressure, and measurement time, that influence thermal conductivity of gas hydrates. As pointed out by English and Tse (2010), for relatively pure hydrates, reducing the porosity of the samples by compacting them is critical for obtaining the reliable thermal conductivity in the intermediate temperature range. For hydrate-bearing sediments, Tzirita (1992) concluded that porosity is also a critical factor in controlling the thermal conductivity.…”
Section: Thermal Conductivity Of Gas Hydratementioning
confidence: 99%
“…Prior to discussing the conductivity results, however, it is worthwhile making some general remarks about crystalline thermal conductivity behaviour, the temperature profile of which is wellknown: above half the Debye temperature,  D /2, the thermal conductivity exhibits a dependence, determined mainly by boundary scatterings. Therefore, experimental determination of thermal conductivity is highly dependent on samples" nature and quality, as outlined in some detail for hydrates [26][27][28][29][30][31][32][33][34], which serves to emphasise the difficulty in direct, quantitative comparisons of theoretical and experimental values, as previous research for hydrates has shown . It must also be borne in mind that experimental measurements of hydrogen hydrate thermal conductivity have not been reported.…”
Section: Thermal Conductivitiesmentioning
confidence: 99%
“…Experimental measurements of thermal conductivity in (type I) methane hydrate exhibit a crystal-like temperature dependence below 90 K, with glass-like behaviour above this temperature [24], while similar low-temperature behaviour is observed in some semi-conductor clathrates [25]. In addition to various recent molecular dynamics (MD) studies estimating methane hydrate thermal conductivities [26][27][28][29][30][31][32][33][34], and those of other clathrates [29,34], progress has been made towards elucidating the underlying mechanisms governing thermal conduction in methane hydrates of various polymorphs [31][32][33]. It was found that a greater extent of damping in guest-host energy transfer in type I methane hydrates as higher temperatures (above 150 K), is responsible for the more glass-like temperature dependence of the thermal conductivity, whereas more harmonic energy transfer at lower temperatures results in the experimentally observed crystal-like behaviour [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…The thermal conductivity of clathrate hydrates have been discussed by English and Tse [8] and the transition behavior and heat capacity of numerous clathrate hydrates at atmospheric conditions have been reviewed by Yamamuro and Suga [9].…”
Section: Host-guest Compoundsmentioning
confidence: 99%